1984
DOI: 10.1172/jci111613
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic messenger ribonucleic acid activity profiles in experimental azotemia in the rat. Relationship to food intake and thyroid function.

Abstract: A b:s tract. We have studied the hepatic messenger RNA (mRNA) activity profile in chronically azotemic rats and sought to determine whether the observed changes could be mediated either by reduced food intake or diminished thyroid function at the tissue level. mRNA activity profiles were produced by twodimensional gel electrophoretic separation of radioactively labeled products of an in vitro reticulocyte lysate system which had been programmed by hepatic RNA. Of the -240 translational products identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…For Lim et al [2], the significant reduction in hepatic nuclear T, content and liver T, receptor-binding capacity in uremic rats with a severe degree of uremia (B U N >I g/1) was consistent with the presence of a selective tissue deficiency of thyroid hormone, in agreement with the observation of reduced activity of two liver enzymes (rx-GPD and ME) known to be under thyroid hormone regulation [1], It is important to note that uremic rats with a less severe degree of uremia (BUN < 1 g/1) showed only a trend to diminution but no statistically significant dif ference in hepatic nuclear Tj content and liver T; recep tor-binding capacity [2], Kinlaw et al [3] observed no significant reduction in the hepatic level of nuclear T, and in the activity of hepatic a-G PD and ME. These findings are consistent with a euthyroidal state of hepatic tissues in uremic rats associated with a normal circulating TSH level.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…For Lim et al [2], the significant reduction in hepatic nuclear T, content and liver T, receptor-binding capacity in uremic rats with a severe degree of uremia (B U N >I g/1) was consistent with the presence of a selective tissue deficiency of thyroid hormone, in agreement with the observation of reduced activity of two liver enzymes (rx-GPD and ME) known to be under thyroid hormone regulation [1], It is important to note that uremic rats with a less severe degree of uremia (BUN < 1 g/1) showed only a trend to diminution but no statistically significant dif ference in hepatic nuclear Tj content and liver T; recep tor-binding capacity [2], Kinlaw et al [3] observed no significant reduction in the hepatic level of nuclear T, and in the activity of hepatic a-G PD and ME. These findings are consistent with a euthyroidal state of hepatic tissues in uremic rats associated with a normal circulating TSH level.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the discrepancy between results of Kinlaw et al [3] and Lim et al [1,2] may be related to the different duration of uremia in both studies (3 and 6 weeks, respec tively) and also to the degree of severity of uremia. A certain degree of uremia seems necessary for thyroid hormone dysfunction to become manifest because changes are more modest in the less azotemic group of rats.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Abnormalities for all these hormones have been described in uremia [41][42][43]. In particular, tissue level hypothyroidism has been found in previous studies [43], although this has not been confirmed in more recent investigations [44], Further information on receptor occupan cy, binding kinetics and postbinding events in uremia are required before the effects of inhibition of Na.K-ATP'ase by hypothetical endogenous inhibitors on the response to ex ogenous digitalis can be assessed. At the mo ment, no clear clinical consequences can be derived from the above considerations.…”
Section: Is the Dose-response Relationship For Digitalis Altered In Umentioning
confidence: 99%